Penentuan Harga Tiket Pesawat Lion Air Perspektif Hukum Ekonomi Syariah - Sherly Karlinda (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2020)
Lion Air is a private company engaged in air transportation. It uses a low-cost concept “Low-Cost Carrier” with the slogan “We Make People Fly”. Airline ticket prices sold on Lion Air airline sites and travel agents often experience significant fluctuations. It can be seen in certain moments, such as Eid, long holidays, and other holidays. This study uses a descriptive qualitative approach. This research is research using a field approach in the form of primary data and secondary data. Meanwhile, data sources obtained using observation, interviews, and documentation. Then analyzed descriptively through, reduction, display and conclusion and prescriptive. The implementation of the principle of determining Lion Air ticket prices includes transactions between airlines and consumers, airlines with travel agents, and travel agents with consumers. The transaction in fiqh is classified as an ijarah contract. The second implementation is related to the ticket component which is closely related to fluctuation. Fluctuations caused by the law of normal supply and demand may have consequences, while fluctuations that occur due to company play are categorized as gharar.